Use of rodents as models of human diseases - Thierry F Vandamme (Wolters Kluwer Medknow Publications, 2014)
Advances in molecular biology have significantly increased the understanding of the biology of different diseases. However, these discoveries have not yet been fully translated into improved treatments for patients with diseases such as cancers. One of the factors limiting the translation of knowledge from preclinical studies to the clinic has been the limitations of in vivo diseases models. In this brief review, we will discuss the advantages and disadvantages of rodent models that have been developed to simulate human pathologies, focusing in models that employ xenografts and genetic modification. Within the framework of genetically engineered mouse (GEM) models, we will review some of the current genetic strategies for modeling diseases in the mouse and the preclinical studies that have already been undertaken. We will also discuss how recent improvements in imaging technologies may increase the information derived from using these GEMs during early assessments of potential therapeutic pathways. Furthermore, it is interesting to note that one of the values of using a mouse model is the very rapid turnover rate of the animal, going through the process of birth to death in a very short timeframe relative to that of larger mammalian species.